Penerapan Metode Everyone Is Teacher Here dalam Upaya Meningkatkan Aktivitas Belajar Siswa pada Mata Pelajaran PAI Materi Pokok Fikih Ibadah - Salman Azkiya Hamzah (Bandung Conference Series: Islamic Education, 2024)
Abstract. Based on observations made by researchers while teaching at MI Nurul Huda, this research was motivated by the lack of student activity in participating in the process of teaching and learning activities in PAI subjects, especially in class VI. According to researchers, this can happen due to a lack of teacher creativity and variations in the use of methods. learning so that teaching and learning activities become monotonous and boring for students. Following up on this problem, researchers provide a solution to student inactivity by offering the application of the everyone is a teacher method here. The aim of this research is to find out: 1) The reality of student learning activities before using the Everyone is Teacher Here method, 2) The process of applying the Everyone is Teacher Here method to Islamic Religious Education (PAI) material in the Jurisprudence of Worship, 3) The reality of student learning activities after using method everyone is a teacher here. Researchers are trying to increase student learning activities by using the Everyone is Teacher Here method with the hope that the steps taken in implementing this method can trigger student activity in teaching and learning activities. This research is included in Classroom Action Research (PTK) using a mixed method approach, namely a qualitative and quantitative approach. Qualitative data collection techniques use interviews and documentation with descriptive data analysis techniques, for quantitative data use data collection techniques using questionnaires and observation with data analysis techniques using a Likert scale. The research results show: 1) The student learning activity questionnaire in PAI subjects before the Everyone is Teacher Here method was implemented was 2.93% with a moderate interpretation, in the interval 2.60 – 3.39. 2) Learning using the Everyone is Teacher method here shows an increase in the results of observations of student learning activities, in cycle I they got a score of 33.3%, then in cycle II they got a score of 100%, so there is a difference. in cycle I and cycle II it was 67.7%. 3) The results of applying the Everyone is Teacher Here method in PAI learning to student learning activities were accumulated during the application of the Everyone is Teacher Here method in cycle I with an average value of 2.93 with a Medium interpretation, in the interval 2.60 – 3.39. This increased in cycle II with an average value of 3.82 with a High interpretation, in the interval 3.40 – 4.19. Thus, it can be concluded that the application of the Everyone is Teacher Here method in the Jurisprudence of Worship subject in class VI MI Nurul Huda Bandung can increase student learning activities. Abstrak. Berdasarkan observasi yang dilakukan oleh peneliti selama mengajar di MI Nurul Huda, penelitian ini dilatarbelakangi oleh kurang aktifnya siswa dalam mengikuti proses kegiatan belajar mengajar pada mata pelajaran PAI khususnya di kelas VI, menurut peneliti hal tersebut bisa terjadi dikarenakan kurangnya kreativitas dan variasi guru dalam penggunaan metode pembelajaran sehingga kegiatan belajar mengajar menjadi monoton dan menjenuhkan bagi siswa. Menindak lanjuti persoalan tersebut peneliti memberi solusi terhadap ketidak aktifan siswa dengan menawarkan penerapan metode everyone is teacher here. Tujuan penelitian ini untuk mengetahui: 1) Realitas aktivitas belajar siswa sebelum menggunakan metode everyone is teacher here, 2) Proses penerapan metode everyone is teacher here pada mata pelajaran Pendidikan Agama Islam (PAI) materi Fikih Ibadah, 3) Realitas aktivitas belajar siswa setelah menggunakan metode everyone is teacher here. Peneliti berupaya meningkatkan aktivitas belajar siswa menggunakan metode everyone is teacher here dengan harapan langkah-langkah yang terdapat dalam pelaksanaan metode tersebut bisa memantik keaktifan siswa dalam kegiatan belajar mengajar. Penelitian ini termasuk ke dalam Penelitian Tindakan Kelas (PTK) dengan menggunakan pendekatan mixed method yaitu pendekatan kualitatif dan kuantitatif. Teknik pengumpulan data kualitatif menggunakan wawancara dan dokumentasi dengan teknik analisis data deskriptif, untuk data kuantitatif menggunakan teknik pengumpulan data menggunakan angket dan observasi dengan teknik analisis data menggunakan skala likert. Hasil penelitian menunjukkan: 1) Angket aktivitas belajar siswa pada mata pelajaran PAI sebelum penerapan metode everyone is teacher here sebesar 2,93% dengan interpretasi sedang, berada pada interval 2,60 – 3,39. 2) Pembelajaran dengan menggunakan metode everyone is teacher here terdapat peningkatan hasil observasi aktivitas belajar siswa, pada siklus I mendapatkan skor 33,3% selanjutnya pada siklus II mendapatkan skor 100% dengan demikian terdapat selisih pada siklus I dan siklus II sebesar 67,7%. 3) Hasil penerapan metode everyone is teacher here pada pelajaran PAI terhadap aktivitas belajar siswa, diakumulasikan pada saat penerapan metode everyone is teacher here siklus I dengan nilai rata-rata 2,93 dengan interpretasi Sedang, berada pada interval 2,60 – 3,39. Hal ini mengalami peningkatan pada siklus II dengan nilai rata-rata 3,82 dengan interpretasi Tinggi, berada pada interval 3,40 – 4,19. Dengan demikian dapat disimpulkan bahwa penerapan metode everyone is teacher here pada pokok bahasan Fikih Ibadah di kelas VI MI Nurul Huda Bandung dapat meningkatkan aktivitas belajar siswa.